Pemberdayaan UMKM di Sentra Industri Kecil Teritip Kota Balikpapan - Anisa, Desta; Nurmiyati, Niken; Akbar, Paisal (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
The development of the Teritip Small Industrial Center in Balikpapan continues to fase several challenges, particularly in optimizing the empowerment of business actors. This study aims to aims to analyze the implementation of industrial center development. The research employed a descriptive qualitative approach, with data collected through interviews, field observations, and decument analysis. The findings reveal three key poins: (1) capacity building for business actors has been carried out through training and facility provision, yet it has not been evenly accessed by micro-scale enterprises; (2) community participation in utilizing the industrial center is relatively active, although marketing and product innovation remain persistent abstacles; and (3) the economic independence of business actors has shown positive progress, despite issues related tp the sustainability of building rental schemes and the affective use of available facilities. In conclusion, the development of the Teritip Small Industrial Center requires strengthened menagement, improved human resource quality, and a review of rental policies to support sustainable local economic empowerment.